Penetration resistance of laminated ceramic/polymer structures - Yadav, S; Ravichandran, G (International journal of impact engineering, 2003)
Ballistic penetration experiments have been performed on ceramic tiles laminated with thin layers of polymer in between. The experiment involves shooting a cylindrical rod made of a tungsten heavy alloy (WHA) against an unconfined ceramic/polymer laminated structure that is backed by a 6061-T6 aluminum alloy cylindrical-block, at a velocity ranging between 1000 to 1200 m/s. The residual depth of penetration in the aluminum block is used as a measure of the resistance offered by the laminated ceramic/polymer structure to ballistic penetration. Penetration resistance of the laminated ceramic/polymer structures is compared to that of monolithic ceramic structures of the same total thickness. Experimental results demonstrate that penetration resistance of an unconfined ceramic structure can be improved significantly by laminating ceramic tiles with thin polymer layers in between. This enhanced performance of the laminated structure is attributed to a reduced wave propagation (and damage) velocity in the laminated ceramic/polymer structure and also to the crack arresting feature of the polymer layer.